Nano engineering and materials technologies. selected, peer reviewed papers from the 8th International Conference on Nanostructures, Nanomaterials and Nanoengineering 2016 (ICNNN 2019) and 4th International Conference on Materials Technology and Applications (ICMTA 2019), October 11-14, 2019, Kyoto, Japan - Gong, Hao (Professor of materials science); Umemura, Kazuo; Lin, Ching-Fuh (Trans Tech Publications Ltd, 2020)
8th International Conference on Nanostructures, Nanomaterials and Nanoengineering (ICNNN 2019) and 4th International Conference on Materials Technology and Applications (ICMTA 2019).
Keywords: Nanostructured materials -- Congresses.; Nanostructures -- Congresses.; Nanotechnology -- Congresses.; Materials science -- Congresses.; Nanomatériaux -- Congrès.; Nanostructures -- Congrès.; Science des matériaux -- Congrès.; Nanotechnologie -- Congrès.; Materials science; Nanostructured materials; Nanostructures; Nanotechnology; Conference papers and proceedings